How mutant isocitrate dehydrogenase orchestrates immune cells - Bunse, Lukas; Platten, Michael (Neuro-Oncology, 2022)
Astrocytomas and oligodendrogliomas, World Health Organization grades 2-4, are signified by recurrent mutations in the genes for mutant isocitrate dehydrogenase (IDH) types 1 and 2. The neomorphic enzymatic activity of mutant IDH causes epigenetic reprogramming by histone and DNA hypermethylation via the excessive production of the oncometabolite R-2-hydroxyglutarate (R-2-HG), ultimately driving dedifferentiation and malignant transformation. Therefore, small molecule mutant IDH inhibitors have been developed to re-differentiate glioma cells in early-stage gliomas.In recent years, a plethora of data has been collected highlighting mutant IDH as a key suppressor of spontaneous and therapy-induced anti-glioma immunity. On the one hand, mutant IDH excludes T cells from the glioma microenvironment (GME) by inhibition of glioma cell signal transducer and activator of transcription 1 (STAT1) transcriptional activity followed by reduced C-X-C motif chemokine ligand 10 (CXCL10)-dependent recruitment of cytotoxic T cells. On the other, its neomorphic enzymatic product R-2-HG incapacitates yet infiltrating T cells by paracrine inhibition of calcium-dependent T cell receptor signaling and polyamine biosynthesis and induces apoptosis of intratumoral T cells.1-3
Online veröffentlicht: 22. November 2021
Gesehen am 03.08.2023